Doom Spending and Financial Independence: Evidence from Across Generation in Indonesia - Ririn Nopiah; Cikit Apriyanti (PT Inovasi Pratama Internasional, 2026)
The rapid expansion of digital technology and social media has fundamentally transformed consumer behavior, contributing to the emergence of doom spending, a compulsive emotional purchasing pattern triggered by stress, negative news exposure, and algorithm-driven content. This study examines generational differences in doom-spending tendencies in Indonesia, focusing on Generation Z, Millennials, and Generation X, and identifies key determinants influencing this behavior within the digital consumption ecosystem. Using data from 300 respondents collected through an online questionnaire, this study applies the Kruskal-Wallis test to assess intergenerational differences and employs ordinal logistic regression to estimate the influence of media use, content exposure, and payment methods on doom spending. The results reveal significant generational variation, with Millennials demonstrating the highest intensity of doom spending, followed by Generation Z and Generation X. The intensity of Facebook use, engagement with product reviews, and exposure to content related to clothing, food and beverages, and gadgets/accessories significantly increase the likelihood of doom spending. Furthermore, the use of cash and credit card payment methods raises the probability of doom-spending behavior, respectively. The findings also show that the majority of purchased items are non-essential goods and that most respondents acknowledge the negative impact of doom spending on their financial independence. This study highlights the urgent need for policy interventions related to financial literacy, digital self-control, and the development of spending-limitation features on social media and e-commerce platforms. Strengthening these aspects is essential, particularly for Millennials, who are identified as the most vulnerable generation.